Room temperature, cavity-free capacitive strong coupling to mechanical motion - Puglia, Denise; Odessey, Rachel H; Burns, Peter; Luhmann, Niklas; Schmid, Silvan; Higginbotham, Andrew P (Nano Letters)
The back-action damping of mechanical motion by electromagnetic radiation is typically overwhelmed by internal loss channels unless demanding experimental ingredients such as superconducting resonators, high-quality optical cavities, or large magnetic fields are employed. Here we demonstrate the first room temperature, cavity-free, all-electric device where back-action damping exceeds internal loss, enabled by a mechanically compliant parallel-plate capacitor with a nanoscale plate separation and an aspect ratio exceeding 1,000. The device has 4 orders of magnitude lower insertion loss than a comparable commercial quartz crystal and achieves a position imprecision rivaling optical interferometers. With the help of a back-action isolation scheme, we observe radiative cooling of mechanical motion by a remote cryogenic load. This work provides a technologically accessible route to high-precision sensing, transduction, and signal processing.

Everyday electromechanics: Capacitive strong coupling to mechanical motion - Puglia, Denise
We introduce a new all-electric platform, that strong couples light to mechanical motion by ensuring that the external environmental coupling dominates over internal mechanical dissipation. The system only has three everyday components: AC, DC, and a fip-chip, in which a metallized silicon nitride membrane is fipped on top of the device under test. This everyday electromechanical device can be operated at low or room temperature and has 10000× lower insertion loss than a comparable commercial quartz crystal, achieves a position imprecision matching state-of-the-art optical interferometer, and enables remote cooling of mechanical motion. The spatial properties of higher order mechanical modes are a promising feature for reconstructing unknown charge distributions.

Room temperature, cavity-free capacitive strong coupling to mechanical motion - Puglia, Denise; Odessey, Rachel H; Burns, Peter S.; Luhmann, Niklas; Schmid, Silvan; Higginbotham, Andrew P (arXiv)
Strong optomechanical coupling -- a regime where mechanical motion is damped by environmental radiation -- has traditionally required demanding experimental ingredients such as superconducting resonators, high-quality optical cavities, or large magnetic fields. Here we demonstrate a room temperature, cavity-free, all-electric device reaching this regime at radio frequencies, enabled by a mechanically compliant parallel-plate capacitor with a nanoscale plate separation and an aspect ratio exceeding 1,000. The device has four orders of magnitude lower insertion loss than a comparable commercial quartz crystal, and achieves a position imprecision rivaling an optical interferometer. With the help of a back-action isolation scheme, we observe radiative cooling of mechanical motion by a remote cryogenic load. This work provides a technologically accessible route to high-precision sensing, transduction, and signal processing.

Superconductivity from a melted insulator in Josephson junction arrays - Mukhopadhyay, Soham; Senior, Jorden L; Saez Mollejo, Jaime; Puglia, Denise; Zemlicka, Martin; Fink, Johannes M; Higginbotham, Andrew P (Nature Physics)
Arrays of Josephson junctions are governed by a competition between superconductivity and repulsive Coulomb interactions, and are expected to exhibit diverging low-temperature resistance when interactions exceed a critical level. Here we report a study of the transport and microwave response of Josephson arrays with interactions exceeding this level. Contrary to expectations, we observe that the array resistance drops dramatically as the temperature is decreased—reminiscent of superconducting behaviour—and then saturates at low temperature. Applying a magnetic field, we eventually observe a transition to a highly resistive regime. These observations can be understood within a theoretical picture that accounts for the effect of thermal fluctuations on the insulating phase. On the basis of the agreement between experiment and theory, we suggest that apparent superconductivity in our Josephson arrays arises from melting the zero-temperature insulator.
Keywords: General Physics and Astronomy

Data for 'Closing of the Induced Gap in a Hybrid Superconductor-Semiconductor Nanowire - Puglia, Denise; Martinez, Esteban; Menard, Gerbold; Pöschl, Andreas; Gronin, Sergei; Gardner, Geoffrey; Kallaher, Ray; Manfra, Michael; Marcus, Charles; Higginbotham, Andrew P; Casparis, Lucas
Data for the manuscript 'Closing of the Induced Gap in a Hybrid Superconductor-Semiconductor Nanowire' ([2006.01275] Closing of the Induced Gap in a Hybrid Superconductor-Semiconductor Nanowire (arxiv.org)) We upload a pdf with extended data sets, and the raw data for these extended datasets as well.

Closing of the induced gap in a hybrid superconductor-semiconductor nanowire - Puglia, Denise; Martinez, E. A.; Ménard, G. C.; Pöschl, A.; Gronin, S.; Gardner, G. C.; Kallaher, R.; Manfra, M. J.; Marcus, C. M.; Higginbotham, Andrew P; Casparis, L. (Physical Review B)
We present conductance-matrix measurements in long, three-terminal hybrid superconductor-semiconductor nanowires, and compare with theoretical predictions of a magnetic-field-driven, topological quantum phase transition. By examining the nonlocal conductance, we identify the closure of the excitation gap in the bulk of the semiconductor before the emergence of zero-bias peaks, ruling out spurious gap-closure signatures from localized states. We observe that after the gap closes, nonlocal signals and zero-bias peaks fluctuate strongly at both ends, inconsistent with a simple picture of clean topological superconductivity.